Crambe meal in supplements for culling cows: animal performance and carcass characteristics - Kennyson Alves de Souza (Acta Scientiarum. Animal Sciences, 2015)
The influence of the replacement of soybean meal by crambe crushed in concentrated supplement at proportions 0, 5, 10, 15%, on the performance and carcass traits of grazing cows is assessed. Within a completely randomized design, twenty Nellore cows, fed on Brachiaria humidicola, were supplemented during the rain-drought transition period and monitored with regard to weight and body conditions every 28 days. Total forage mass and percentages of leaf, stem and senescent material were quantified in loco. The estimation of forage quality consumed by animals was performed by the simulated grazing method. There were no significant differences between the levels of inclusion of crambe crushed on animal performance or carcass characteristics. Replacement did not affect weight, carcass yield, Brazilian commercial cuts, morphometric measures of carcass, characteristics of loins, thickness of carcass fat, perirenalpelvic fat and total meat. Replacement of soybean meal by crambe crushed up to 15% in the concentrated supplement does not affect performance and carcass characteristics of cows finished on pasture.